Immediate outcome, long‐term function and quality of life after extended colectomy with ileorectal or ileosigmoid anastomosis. (August 2014) - Duclos, J.; Lefevre, J. H.; Lefrançois, M.; Lupinacci, R.; Shields, C.; Chafai, N.; Tiret, E.; Parc, Y.
Abstract Aim Total/subtotal colectomy with ileorectal (IRA) or ileosigmoid (ISA) anastomosis is associated with various reported rates of morbidity, function and quality of life. Our object was to determine these end‐points in a series of patients undergoing these operations in our institution. Method All patients who underwent IRA or ISA between 1994 and 2009 were retrospectively reviewed. Results A total of 320 patients (female 49%) with a median age of 54.2 (16.8–90.6) years underwent 338 IRA or ISA (in 18 patients the anastomosis was done twice) for inflammatory bowel disease (n = 96), polyposis (n = 95) and colorectal cancer (n = 97). Mortality and morbidity rates were 1.2% (n = 4) and 19.5% (n = 66) and 47 surgical complications (13.9%) occurred, including 26 (7.7%) cases of anastomotic leakage, leading to 23 re‐operations. After a median follow‐up of 49 (0–196) months, 262 patients still had a functioning anastomosis; 45 patients had died and 13 had a proctectomy. Information on function was obtained in 51.4% (133/259) of the cohort after a median follow‐up of 77 (10–196) months. The mean (± standard deviation) rates of 24 h and nocturnal defaecation were 3.6 ± 2.4 and 0.5 ± 0.9. A disturbance of faecal or flatus continence occurred in 20% and 21% of patients. There was no case of faecal incontinence to solid stool. The mean SF‐36 Physical and Mental Health Summary Scales were 46.3 ± 9.3 and 51.9 ± 9.3. Multivariate analysis showed that IRA and inflammatory bowel disease were both independently associated with poorer long‐term function. Conclusion Colectomy with IRA or ISA is safe with low postoperative morbidity and mortality. The employment of IRA and inflammatory bowel disease appear to be independent negative factors on function in multivariate analysis.